A brief review of entrepreneur roles, innovation and venture capital intermediation and a framework for a proposed venture capital fund. - Tan, Frankie Siew Teck. (2008)
The linkages between entrepreneurs, innovation and capital intermediation are the topics of this report. A framework for a venture fund information memorandum is also included.